KEPEMILIKAN TANAH SECARA PARULOSAN DENGAN PEMBERIAN BATU SULANG PADA MASYARAKAT BATAK TOBA (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 3293 K/PDT/2017) - BERNADETTE AGUSTINA SAGALA (jurnal.unprimdn.ac.id, 2021)
Customary law communities in their customary environment generally carry on the customs that have been passed down from generation to generation from the past and have developed until now. This also applies to the Toba Batak indigenous people in North Sumatra. The Batak Toba community is a genealogical legal community, namely an organized community unit, where the members are bound to a common lineage from one ancestor, either directly because of blood relations (descendants) or indirectly because of marital ties or customary ties. [Hilman Hadikusuma, Introduction to Indonesian Customary Law. In carrying out the customs that exist in the Toba Batak indigenous people, a customary institution is known, namely dalihan natolu. Dalihan Na Tolu is a kinship in the Toba Batak community. This system consists of three elements whose composition consists of dongan tubu or dongan sauntunga, namely people who are of the same clan (brethren of the clan), hula-hula, namely the wife who gives the wife (the wife's parents), and boru, which is the wife who receives or takes wife of a clan group. [Bungaran Antonius Simanjuntak, Meaning of Land Functions for the Batak Toba, Karo, Simalungun community. In the Toba Batak community, the term Parulosan is also known. Ulos is a piece of woven cloth, which is very likely to have existed long ago in the life of the Batak people, especially the Toba Batak. In addition, the term available in the Toba Batak language on ulos contains the meaning of the word about weaving.